Double-layer coated lithium supplement agent as well as preparation method and application thereof
By using double-layer coating technology on the positive electrode lithium supplement agent of lithium ion batteries, the first layer of polymer and lithium salt and the second layer of hydrophobic material, the low conduction efficiency and poor compatibility in lithium ion batteries are solved. Problem, improving battery safety and cycle stability.
Patent Information
- Application Number
- CN202411358222.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium-ion battery positive electrode lithium supplement agents have problems such as low lithium ion conduction efficiency, poor air stability and poor compatibility with electrolyte, which affects the safety and cycle life of the battery.
Use a double-layer coated lithium supplement agent. The first layer consists of polymer and lithium salt, which enhances lithium ion conduction through hydrogen bonds and/or coordination bonds. The second layer consists of hydrophobic materials, providing protection functions and precise use of LBL technology. Control the thickness of the cladding to improve compatibility and stability.
It improves lithium ion conduction efficiency and air stability, enhances compatibility with electrolyte, reduces safety and cycle life problems caused by side reactions, and achieves more efficient lithium ion battery performance.
Smart Images

Figure CN119252920A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a double-layer coated lithium supplement agent and a preparation method and application thereof. Background Art
[0002] As the core energy storage device for modern portable electronic devices, electric vehicles and large-scale energy storage systems, lithium-ion batteries (LIBs) have undergone significant technological innovation and market expansion in recent years. However, the continuous improvement of battery performance and the guarantee of safety remain major challenges facing researchers. Among them, the problem of lithium loss is particularly prominent, which not only limits the cycle efficiency and life of the battery, but also affects the overall energy density of the battery.
[0003] Lithium loss mainly comes from the formation of SEI (solid electrolyte interface) film during the first charge and discharge process of the battery, as well as the irreversible loss of lithium ions due to side reactions during the cycle. Therefore, developing effective lithium replenishment technology to replenish the lithium consumed by the battery during use has become the key to improving battery performance and extending battery life.
[0004] The introduction of positive electrode lithium supplements aims to compensate for the lithium loss caused by side reactions during the charge and discharge process of the battery by pre-adding additional lithium sources to the positive electrode side of the battery, thereby improving the initial efficiency and cycle stability of the battery. However, traditional lithium supplements face multiple challenges in practical applications, including low lithium ion conduction efficiency, poor air stability, and poor compatibility with electrolytes. These problems not only limit the effectiveness of lithium supplements, but may also cause safety hazards such as internal short circuits and thermal runaway in the battery, seriously affecting the safety and reliability of the battery.
[0005] In the field of lithium-ion batteries, the coating technology of positive electrode lithium supplements has received extensive attention, aiming to improve the performance of lithium supplements through a coating layer. For example, CN117154097A discloses a coated positive electrode lithium supplement and a preparation method thereof, wherein the coated positive electrode lithium supplement comprises a core and a coating layer located on the surface of the core, wherein the material of the core comprises Li5FeO4, and the material of the coating layer comprises a lithium halide compound, a solid electrolyte or a super-hydrophobic material. By coating the surface of the lithium supplement Li5FeO4 with a lithium halide compound, a solid electrolyte or a super-hydrophobic material, the problem of Li5FeO4 deteriorating in contact with air, thereby affecting its capacity, is avoided. However, it still has problems such as low lithium ion conduction efficiency and poor compatibility with the electrolyte.
[0006] CN116314816A discloses a positive electrode lithium supplement, its preparation method and application. The positive electrode lithium supplement includes a substrate, a first coating layer and a second coating layer coated on the surface of the substrate from the inside to the outside, and the collective material includes Li2NiO2, the first coating layer is an amorphous carbon layer, and the second coating layer is Mx B layer, the positive electrode lithium supplement is Li2NiO2@C@M x B, where M is a transition metal element. In the positive electrode lithium supplement, the uniform carbon and boride metallic glass double coating layer can effectively improve the conductivity of Li2NiO2 as a whole, reduce the occurrence of side reactions with the electrolyte, and avoid the dissolution of Ni element during the charge and discharge process, thereby effectively reducing the residual alkali content on the surface of the Li2NiO2 positive electrode lithium supplement, while improving its processing performance in the slurry process and the electrochemical performance when applied to lithium-ion batteries.
[0007] Therefore, providing a lithium supplement that takes into account high lithium ion conduction efficiency, poor air stability, and poor compatibility with the electrolyte is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a double-layer coated lithium supplement agent and a preparation method and application thereof.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a double-layer coated lithium supplement agent, the double-layer coated lithium supplement agent comprising a lithium supplement agent core and a first layer coated on the surface of the lithium supplement agent core, the surface of the first layer being coated with a second layer;
[0011] The first layer includes a polymer and a lithium salt, the second layer includes a hydrophobic material, and hydrogen bonds and / or coordination bonds are formed between the lithium salt and the polymer.
[0012] The lithium supplement agent of the present invention is double-coated, and the lithium ion conduction enhancement function of the first layer and the hydrophobic protection function of the second layer are utilized. The two synergistically enhance each other, thereby improving the lithium ion conduction efficiency of the lithium supplement agent, and improving the air stability of the lithium supplement agent, and ensuring good compatibility with the electrolyte and the first layer, thereby avoiding the problem of reduced battery safety and cycle life caused by side reactions.
[0013] In the present invention, the polymer has polar groups (such as ether groups, cyano groups, ester groups, hydroxyl groups, carboxyl groups, etc.), which can react with lithium ions (Li + ) to form coordination bonds, stabilize lithium ions, promote the migration of lithium ions between polymer chains, reduce polarization, and improve the capacity and rate performance of lithium supplements. At the same time, the polar groups can react with anions in lithium salts (such as TFSI - ) form hydrogen bonds to further stabilize the complex structure.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(oxalatoborate) (LiBOB) and lithium difluorooxalatoborate (LiDFOB).
[0016] Preferably, the polymer includes at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA) and polyphenylene ether (PPO).
[0017] Preferably, the molecular weight of the polymer is between 100,000 and 1,000,000 Da, for example, 100,000 Da, 200,000 Da, 300,000 Da, 400,000 Da, 500,000 Da, 600,000 Da, 700,000 Da, 800,000 Da, 900,000 Da or 1,000,000 Da, etc.
[0018] Preferably, the thickness of the first layer is 20-500nm, for example, it can be 20nm, 30nm, 50nm, 60nm, 80nm, 100nm, 125nm, 150nm, 170nm, 180nm, 200nm, 230nm, 260nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.
[0019] Preferably, the hydrophobic material includes at least one of polysiloxane (PDMS), polystyrene (PS), polyparaphenylene (PPTA) and polyisoprene (PI). These hydrophobic materials can form coordination bonds with lithium ions, and using these materials for the second layer coating has the following advantages: they have good compatibility with lithium supplements and electrolytes, avoid the occurrence of side reactions, and improve the overall safety and cycle stability of the battery. Preferably, the molecular weight of the hydrophobic material is between 20,000 and 200,000 Da, for example, it can be 20,000 Da, 30,000 Da, 40,000 Da, 50,000 Da, 60,000 Da, 70,000 Da, 80,000 Da, 90,000 Da, 100,000 Da, 110,000 Da, 120,000 Da, 130,000 Da, 140,000 Da, 150,000 Da, 160,000 Da, 170,000 Da, 180,000 Da, 190,000 Da or 200,000 Da, etc.
[0020] Preferably, the thickness of the second layer is 20-800nm, for example, it can be 20nm, 30nm, 50nm, 60nm, 80nm, 100nm, 125nm, 150nm, 170nm, 180nm, 200nm, 230nm, 260nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm or 800nm, etc.
[0021] Preferably, the mass ratio of the polymer, the lithium salt and the hydrophobic material is (1-10):1:(6-40), wherein the selection range of the polymer is "1-10", for example, it can be 1, 2, 3, 4, 4.5, 5, 6, 7, 8, 9 or 10, etc.; the selection range of the hydrophobic material is "6-40", for example, it can be 6, 8, 9, 10, 12, 13, 15, 16, 17, 18, 20, 22, 23, 25, 27, 28, 30, 32, 34, 35, 36, 38 or 40, etc.
[0022] Preferably, the mass ratio of the polymer to the lithium salt is (5-10):1.
[0023] Preferably, the mass ratio of the lithium salt to the hydrophobic material is 1:(6-20).
[0024] Preferably, the lithium supplement core includes at least one of LiBH4, LiAlH4, Li2SiH6, Li5FeO4, Li3PO4, Li2C4O4, Li2C2O4 and Li2NiO2.
[0025] Preferably, the particle size D50 of the lithium supplement agent core is between 1-20 μm. For example, the particle size D50 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm or 20 μm, etc.
[0026] In a second aspect, the present invention provides a method for preparing the double-layer coated lithium supplement agent as described in the first aspect, the preparation method comprising the following steps:
[0027] (1) dissolving the polymer and the lithium salt in an anhydrous solvent to obtain a first mixed solution;
[0028] (2) mixing the lithium supplement material with the first mixed solution to obtain a second mixed solution;
[0029] (3) Mixing the hydrophobic material with the second mixed solution to complete the coating and obtain a double-layer coated lithium supplement agent.
[0030] The method of the present invention uses LBL (Layer-by-Layer) technology to achieve double-layer coating of the positive electrode lithium supplement. Compared with the traditional coating method, the method of the present invention can accurately control the thickness of each coating layer, thereby avoiding the coating layer being too thick or too thin, affecting the release rate of lithium ions and the overall performance of the lithium supplement. Moreover, the method of the present invention can ensure the uniformity of the coating layer, and improve the stability and efficiency of the lithium supplement.
[0031] The method of the present invention has mild conditions and is easy to operate, does not involve high temperature, high pressure or complex chemical reactions, reduces preparation costs and operation difficulties. The number and thickness of the coating layer can be adjusted, achieving the performance adjustability of the lithium supplement agent.
[0032] Preferably, the double-layer coating of the lithium supplement agent is carried out at a humidity lower than 0.1% RH and under the protection of protective gas. Since the lithium supplement agent is extremely sensitive to water, the method of the present invention should be carried out in a dry environment to ensure that the activity of the lithium supplement agent is not damaged.
[0033] Preferably, the protective gas includes at least one of helium (Ar), argon (He), nitrogen (N2) and neon (Ne).
[0034] Preferably, in step (2), the lithium supplement material is mixed with the first mixed solution in the form of a solution. The uniformity of the mixing can be improved by preliminarily dispersing the lithium supplement material in a solvent to form a solution and then mixing it with the first mixed solution.
[0035] Preferably, the mixing method in step (2) is: stirring at 50-65°C (for example, 50°C, 52°C, 55°C, 58°C, 60°C, 63°C or 65°C, etc.) for 1-2h (for example, 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h or 2h, etc.).
[0036] Preferably, the mixing method in step (3) is: stirring at 50-65°C (for example, 50°C, 52°C, 55°C, 58°C, 60°C, 63°C or 65°C, etc.) for 1-2h (for example, 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h or 2h, etc.).
[0037] In a third aspect, the present invention provides a positive electrode, wherein the positive electrode comprises a positive electrode lithium replenisher, wherein the positive electrode lithium replenisher comprises the double-layer lithium replenisher described in the first aspect.
[0038] In a fourth aspect, the present invention provides a lithium-ion battery, characterized in that the lithium-ion battery comprises the positive electrode described in the third aspect.
[0039] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The lithium supplement agent of the present invention is double-layer coated, utilizing the lithium ion conduction enhancement function of the first layer and the hydrophobic protection function of the second layer. The two synergistically enhance each other, thereby improving the lithium ion conduction efficiency of the lithium supplement agent and improving the air stability of the lithium supplement agent. It also ensures good compatibility with the electrolyte and the first layer, thereby avoiding the problem of reduced battery safety and cycle life caused by side reactions.
[0042] (2) The method of the present invention uses LBL technology to achieve double-layer coating of the positive electrode lithium supplement. Compared with the traditional coating method, the method of the present invention can accurately control the thickness of each coating layer, thereby avoiding the coating layer being too thick or too thin, affecting the release rate of lithium ions and the overall performance of the lithium supplement. Moreover, the method of the present invention can ensure the uniformity of the coating layer, thereby improving the stability and efficiency of the lithium supplement.
[0043] (3) The method of the present invention has mild conditions and is easy to operate. It does not involve high temperature, high pressure or complex chemical reactions, which reduces the preparation cost and operation difficulty. The number and thickness of the coating layer can be adjusted, achieving the performance adjustability of the lithium supplement agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic structural diagram of a double-layer coated lithium supplement agent in one embodiment of the present invention. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0046] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Example 1
[0048] This embodiment provides a double-layer coated lithium supplement agent, such as Figure 1 As shown, the double-layer coated lithium supplement agent comprises a lithium supplement agent core 1 and a first layer 2 coated on the surface of the lithium supplement agent core 1, and the surface of the first layer 2 is coated with a second layer 3;
[0049] The first layer 2 includes a polymer and a lithium salt, the polymer has a polar group, the second layer 3 includes a hydrophobic material, a hydrogen bond and / or a coordination bond is formed between the lithium salt and the polymer, and a coordination bond is formed between the lithium salt and the hydrophobic material;
[0050] The core of the lithium supplement is Li5FeO4, the lithium salt is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), the polymer is polyethylene oxide (PEO, molecular weight 500000Da), and the hydrophobic material is polysiloxane (PDMS, molecular weight 100000Da).
[0051] The mass ratio of polymer, lithium salt and hydrophobic material is 10:1:10;
[0052] The particle size D50 of the lithium supplement core is 10 μm, the thickness of the first layer is 100 nm, and the thickness of the second layer is 700 nm.
[0053] This embodiment also provides a method for preparing the above-mentioned composite positive electrode material, comprising the following steps:
[0054] Preparation: All operations should be performed in an inert gas atmosphere and the ambient humidity should be kept below 0.1% RH.
[0055] Preparation of PEO-LiTFSI composite material: PEO and LiTFSI were added to anhydrous acetonitrile in a mass ratio of 10:1, heated to 60°C under magnetic stirring, and stirred continuously until PEO and LiTFSI were completely dissolved to form a transparent solution to obtain a PEO-LiTFSI solution.
[0056] Dispersion of positive electrode lithium supplement agent: Weigh an appropriate amount of lithium supplement agent Li5FeO4, add it to a small amount of anhydrous solvent, ensure that the lithium supplement agent is completely dispersed, and obtain Li5FeO4 dispersion.
[0057] Primary coating: Add the Li5FeO4 dispersion into the PEO-LiTFSI solution and continue stirring at 60°C for 2h to allow the surface of the lithium supplement agent to evenly adsorb the PEO-LiTFSI composite material to obtain a precursor solution.
[0058] Secondary coating: Add the secondary coating material PDMS into the precursor solution, with the mass ratio of PEO:LiTFSI:PDMS being 10:1:10, and continue stirring at 60°C for 2h to complete the coating.
[0059] Drying and curing: The lithium supplement agent after secondary coating is placed in a vacuum drying oven and dried at 40° C. for 12 hours to ensure that the solvent is completely removed and the composite material is cured to obtain the double-layer coated lithium supplement agent.
[0060] Example 2
[0061] This embodiment provides a double-layer coated lithium supplement agent, which is different from Embodiment 1 in that the mass ratio of the polymer, the lithium salt and the hydrophobic material is 6:1:10.
[0062] Example 3
[0063] This embodiment provides a double-layer coated lithium supplement agent, which is different from Embodiment 1 in that the mass ratio of the polymer, the lithium salt and the hydrophobic material is 10:1:6.
[0064] Example 4
[0065] This embodiment provides a double-layer coated lithium supplement agent, which is different from Embodiment 1 in that the mass ratio of the polymer to the lithium salt is 4:1, and the mass ratio of the lithium salt to the hydrophobic material is the same as that of Embodiment 1.
[0066] Example 5
[0067] This embodiment provides a double-layer coated lithium supplement agent, which is different from Embodiment 1 in that the mass ratio of the polymer to the lithium salt is 11:1, and the mass ratio of the lithium salt to the hydrophobic material is the same as that of Embodiment 1.
[0068] Example 6
[0069] This embodiment provides a double-layer coated lithium supplement agent, which is different from Embodiment 1 in that the mass ratio of lithium salt to hydrophobic material is 1:21, and the mass ratio of polymer to lithium salt is the same as that of Embodiment 1.
[0070] Example 7
[0071] This embodiment provides a double-layer coated lithium supplement agent, the double-layer coated lithium supplement agent comprising a lithium supplement agent core and a first layer coated on the surface of the lithium supplement agent core, the surface of the first layer being coated with a second layer;
[0072] The first layer includes a polymer and a lithium salt, the polymer has a polar group, the second layer includes a hydrophobic material, a hydrogen bond and / or a coordination bond is formed between the lithium salt and the polymer, and a coordination bond is formed between the lithium salt and the hydrophobic material;
[0073] The core of the lithium supplement is Li5FeO4, the lithium salt is lithium trifluoromethanesulfonate (LiCF3SO3), the polymer is polyacrylonitrile (PAN, molecular weight is 500000Da), and the hydrophobic material is polystyrene (PS, molecular weight is 100000Da);
[0074] The mass ratio of polymer, lithium salt and hydrophobic material is 5:1:20;
[0075] The particle size D50 of the lithium supplement core is 10 μm, the thickness of the first layer is 100 nm, and the thickness of the second layer is 700 nm.
[0076] This embodiment also provides a method for preparing the above-mentioned composite positive electrode material, comprising the following steps:
[0077] Preparation: All operations should be performed in an inert gas atmosphere and the ambient humidity should be kept below 0.1% RH.
[0078] Preparation of PAN-LiCF3SO3 composite material: PAN and LiCF3SO3 were added to anhydrous acetonitrile in a mass ratio of 5:1, heated to 65°C under magnetic stirring, and stirred continuously until PAN and LiCF3SO3 were completely dissolved to form a transparent solution to obtain a PAN-LiCF3SO3 solution.
[0079] Positive electrode lithium supplement agent dispersion: Weigh an appropriate amount of lithium supplement agent LiBH4, add it to a small amount of anhydrous solvent, ensure that the lithium supplement agent is completely dispersed, and obtain a LiBH4 dispersion.
[0080] Primary coating: Add the LiBH4 dispersion into the PAN-LiCF3SO3 solution and continue stirring at 65°C for 1.5h to allow the surface of the lithium supplement agent to evenly adsorb the PAN-LiCF3SO3 composite material to obtain a precursor solution.
[0081] Secondary coating: Add the secondary coating material PS into the precursor solution, with the mass ratio of PAN:LiTFSI:PS being 5:1:20, and continue stirring at 55°C for 2h to complete the coating.
[0082] Drying and curing: The lithium supplement agent after secondary coating is placed in a vacuum drying oven and dried at 50° C. for 10 hours to ensure that the solvent is completely removed and the composite material is cured to obtain the double-layer coated lithium supplement agent.
[0083] Example 8
[0084] This embodiment provides a double-layer coated lithium supplement agent, the double-layer coated lithium supplement agent comprising a lithium supplement agent core and a first layer coated on the surface of the lithium supplement agent core, the surface of the first layer being coated with a second layer;
[0085] The first layer includes a polymer and a lithium salt, the polymer has a polar group, the second layer includes a hydrophobic material, a hydrogen bond and / or a coordination bond is formed between the lithium salt and the polymer, and a coordination bond is formed between the lithium salt and the hydrophobic material;
[0086] The core of the lithium supplement is Li2SiH6, the lithium salt is lithium difluorooxalate borate (LiDFOB), the polymer is polymethyl methacrylate (PMMA, molecular weight 300000Da), and the hydrophobic material is polyisoprene (PI, molecular weight 150000Da);
[0087] The mass ratio of polymer, lithium salt and hydrophobic material is 8:1:15;
[0088] The particle size D50 of the lithium supplement core is 5 μm, the thickness of the first layer is 300 nm, and the thickness of the second layer is 150 nm.
[0089] This embodiment also provides a method for preparing the above-mentioned composite positive electrode material, comprising the following steps:
[0090] Preparation: All operations should be performed in an inert gas atmosphere and the ambient humidity should be kept below 0.1% RH.
[0091] Preparation of PMMA-LiDFOB composite material: PMMA and LiTFSI were added to anhydrous acetonitrile in a mass ratio of 8:1, heated to 60°C under magnetic stirring, and stirred continuously until PMMA and LiDFOB were completely dissolved to form a transparent solution to obtain a PMMA-LiTFSI solution.
[0092] Dispersion of positive electrode lithium supplement agent: Weigh an appropriate amount of lithium supplement agent Li2NiO2, add it to a small amount of anhydrous solvent, ensure that the lithium supplement agent is completely dispersed, and obtain Li2NiO2 dispersion.
[0093] Primary coating: Add the Li2NiO2 dispersion into the PMMA-LiDFOB solution and continue stirring at 60°C for 1 hour to allow the PMMA-LiDFOB composite material to be uniformly adsorbed on the surface of the lithium supplement agent to obtain a precursor solution.
[0094] Secondary coating: Add the secondary coating material PI into the precursor solution, with the mass ratio of PMMA:LiDFOB:PI being 8:1:15, and continue stirring at 55°C for 2h to complete the coating.
[0095] Drying and curing: The lithium supplement agent after secondary coating is placed in a vacuum drying oven and dried at 55° C. for 8 hours to ensure that the solvent is completely removed and the composite material is cured to obtain the double-layer coated lithium supplement agent.
[0096] Comparative Example 1
[0097] This comparative example is an uncoated lithium supplement Li5FeO4.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 1 is that the first layer is not included.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 1 is that the second layer is not included.
[0102] Performance Testing:
[0103] Ⅰ.Electrical performance verification:
[0104] The lithium supplement agents of Examples 1-6 and Comparative Examples 1-3 were used as positive electrode materials to assemble 2032 button half-cells, wherein the positive electrode material: PVDF: SP (mass ratio) = 89.5:5:5, NMP was added, and after degassing treatment, a positive electrode slurry was obtained, and the positive electrode slurry was coated on the surface of aluminum foil, dried and rolled to obtain a positive electrode sheet, and a metal lithium sheet was used as a counter electrode to obtain a button cell. The charge and discharge test was performed on it, and the voltage window was 2.0-4.4V. The results are shown in Table 1:
[0105] Table 1
[0106] 1C charging capacity mAh / g 3C charging capacity mAh / g Example 1 711 679 Example 2 667 610 Example 3 712 683 Example 4 641 595 Example 5 704 676 Example 6 572 508 Example 7 644 601 Example 8 661 607 Comparative Example 1 609 554 Comparative Example 2 602 527 Comparative Example 3 718 687
[0107] The results show that the lithium supplement of the present invention is double-coated, and the lithium ion conduction enhancement function of the first layer and the hydrophobic protection function of the second layer are utilized. The two synergistically enhance the efficiency of the lithium ion conduction of the lithium supplement. The battery assembled with the lithium supplement has high capacity and good rate performance. The gram capacity of 1C charging can reach more than 644mAh / g, and the gram capacity of 3C charging can reach more than 600mAh / g.
[0108] At the same time, by comparing Examples 1-2 with Examples 4-5, it can be seen that when the mass ratio of the polymer to the lithium salt is (5-10): 1, the effect is better. When the polymer coating amount is sufficient, the capacity and rate performance of the lithium supplement agent are better, indicating that the polymer and the lithium salt surface form a coating layer with a lithium ion conduction enhancement function, which is beneficial to the performance of the lithium supplement agent. However, the excessive amount of polymer coating in Example 5 will lead to a decrease in the proportion of active substances, that is, a decrease in capacity. In Example 6, the amount of hydrophobic material used is too much, resulting in a decrease in the proportion of active substances and a decrease in the overall capacity of the material.
[0109] By comparing Example 1 with Comparative Example 1, it can be seen that by double-coating the lithium supplement agent, not only the capacity and rate performance of the material can be improved.
[0110] By comparing Example 1 with Comparative Example 2, it can be seen that the first layer of coating can reduce polarization and improve the capacity and rate performance of the lithium supplement agent.
[0111] Ⅱ. Water absorption verification
[0112] The lithium supplement was exposed to an environment at 25°C and a humidity of about 40% RH. After a period of time, the moisture content of the lithium supplement was tested. The results are shown in Table 2:
[0113] Table 2
[0114] Initial moisture value / ppm Moisture value after exposure for 2 hours / ppm Example 1 454 634 Example 2 433 598 Example 3 489 822 Example 4 428 602 Example 5 437 617 Example 6 443 510 Example 7 437 507 Example 8 429 522 Comparative Example 1 462 1302 Comparative Example 2 460 662 Comparative Example 3 457 1287
[0115] The results show that when the lithium supplement has a hydrophobic coating, its water absorption capacity is significantly reduced, which is beneficial to the storage and stability of the lithium supplement. After exposure for 2 hours, the moisture value is below 822ppm.
[0116] At the same time, by comparing Examples 1-2 with Examples 3 and 6, it can be seen that the hydrophobic effect is better when the mass ratio of lithium salt to the hydrophobic material is 1:(10-20). The amount of hydrophobic material used in Example 3 is too small, resulting in the lithium supplement material absorbing water too quickly.
[0117] By comparing Example 1 with Comparative Example 1, it can be seen that by double-coating the lithium supplement agent, not only can the capacity and rate performance of the material be improved, but the water absorption can also be reduced, which is beneficial to improving the environmental stability of the lithium supplement agent.
[0118] By comparing Example 1 with Comparative Example 3, it can be seen that the second layer of coating can reduce the water absorption of the material and improve its environmental stability.
[0119] In summary, the present invention describes the experimental design and method in detail, and confirms the effectiveness and superiority of the double-layer coating technology through electrochemical performance tests and water absorption tests.
[0120] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A double-layer coated lithium supplement agent, characterized in that: The double-layer coated lithium supplement agent comprises a lithium supplement agent core and a first layer coated on the surface of the lithium supplement agent core, and the surface of the first layer is coated with a second layer; The first layer includes a polymer and a lithium salt, the polymer has a polar group, the second layer includes a hydrophobic material, and a hydrogen bond and / or a coordination bond is formed between the lithium salt and the polymer.
2. The double-layer coated lithium supplement agent according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate) and lithium difluorooxalatoborate; Preferably, the polymer comprises at least one of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate and polyphenylene ether; Preferably, the molecular weight of the polymer is between 100,000 and 1,000,000 Da; Preferably, the thickness of the first layer is 20-500 nm.
3. The double-layer coated lithium supplement agent according to claim 1 or 2, characterized in that: The hydrophobic material comprises at least one of polysiloxane, polystyrene, polyparaphenylene and polyisoprene; Preferably, the molecular weight of the hydrophobic material is between 20,000 and 200,000 Da; Preferably, the second layer has a thickness of 20-800 nm.
4. The double-layer coated lithium supplement according to any one of claims 1 to 3, characterized in that: The mass ratio of the polymer, the lithium salt and the hydrophobic material is (1-10):1:(6-40); Preferably, the mass ratio of the polymer to the lithium salt is (5-10):1; Preferably, the mass ratio of the lithium salt to the hydrophobic material is 1:(6-20).
5. The double-layer coated lithium supplement agent according to any one of claims 1 to 4, characterized in that: The lithium supplement core includes at least one of LiBH4, LiAlH4, Li2SiH6, Li5FeO4, Li3PO4, Li2C4O4, Li2C2O4 and Li2NiO2; Preferably, the particle size D50 of the lithium supplement core is between 1-20 μm.
6. A method for preparing a double-layer coated lithium supplement agent according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) dissolving the polymer and the lithium salt in an anhydrous solvent to obtain a first mixed solution; (2) mixing the lithium supplement material with the first mixed solution to obtain a second mixed solution; (3) Mixing the hydrophobic material with the second mixed solution to complete the coating and obtain a double-layer coated lithium supplement agent.
7. The preparation method according to claim 6, characterized in that: The double-layer coating of the lithium supplement agent is carried out at a humidity lower than 0.1% RH and under the protection of a protective gas; Preferably, the protective gas includes at least one of helium, argon, nitrogen and neon.
8. The preparation method according to claim 6 or 7, characterized in that: In step (1), the concentration of the polymer in the first mixed solution is 5-15 wt %; Preferably, in step (2), the lithium supplement material is mixed with the first mixed solution in the form of a solution. Preferably, the mixing method in step (2) is: stirring at 50-65° C. for 1-2 h; Preferably, the mixing method in step (3) is: stirring at 50-65° C. for 1-2 h.
9. A positive electrode, characterized in that: The positive electrode includes a positive electrode lithium replenisher, and the positive electrode lithium replenisher includes the double-layer lithium replenisher according to any one of claims 1 to 5.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode according to claim 9.
Citation Information
Cited By
Lithium-rich material, preparation method thereof, positive pole piece containing lithium-rich material, secondary battery and electric device
CN121331832A
Lithium-rich material, preparation method thereof, and positive electrode sheet, secondary battery, and electric device comprising the lithium-rich material
CN121331832B
Gradient composite coated anode lithium supplement agent and preparation method and application thereof
CN121790560A
A gradient composite-coated positive electrode lithium supplementing agent, a preparation method and application thereof
CN121790560B
